A Pseudomonas aeruginosa TIR effector mediates immune evasion by targeting UBAP1 and TLR adaptors. (8th May 2017) - Imbert, Paul RC; Louche, Arthur; Luizet, Jean‐Baptiste; Grandjean, Teddy; Bigot, Sarah; Wood, Thomas E; Gagné, Stéphanie; Blanco, Amandine; Wunderley, Lydia; Terradot, Laurent; Woodman, Philip; Garvis, Steve; et al.
Abstract: Bacterial pathogens often subvert the innate immune system to establish a successful infection. The direct inhibition of downstream components of innate immune pathways is particularly well documented but how bacteria interfere with receptor proximal events is far less well understood. Here, we describe a Toll/interleukin 1 receptor (TIR) domain‐containing protein (PumA) of the multi‐drug resistant Pseudomonas aeruginosa PA7 strain. We found that PumA is essential for virulence and inhibits NF‐κB, a property transferable to non‐PumA strain PA14, suggesting no additional factors are needed for PumA function. The TIR domain is able to interact with the Toll‐like receptor (TLR) adaptors TIRAP and MyD88, as well as the ubiquitin‐associated protein 1 (UBAP1), a component of the endosomal‐sorting complex required for transport I (ESCRT‐I). These interactions are not spatially exclusive as we show UBAP1 can associate with MyD88, enhancing its plasma membrane localization. Combined targeting of UBAP1 and TLR adaptors by PumA impedes both cytokine and TLR receptor signalling, highlighting a novel strategy for innate immune evasion. Synopsis: PumA is a TIR domain‐containing protein required for virulence of the multidrug resistant Pseudomonas aeruginosa PA7 strain. PumA interacts with TLR adaptors but also UBAP1, targeting ESCRT‐I to simultaneously inhibit TLR and TNFR1 signalling. PumA is a virulence factor of multidrug resistant Pseudomonas aeruginosa PA7 strain. PumA mediates inhibition of NFkB and TNFR1 signalling during infection in vitro . The TIR domain of PumA enables interaction with the TLR adaptor TIRAP but most remarkably with the ESCRT‐I component UBAP1. UBAP1 also associates with MyD88 and can impact intracellular sorting of this adaptor. Abstract : PumA from a multi‐drug resistant bacterial strain subverts the host innate immune system through interference with NF‐κB activation by both Toll‐like receptors and inflammatory cytokine receptors.